Self-navigated versus navigator-gated 3D MRI sequence for non-enhanced aortic root measurement in transcatheter aortic valve implantation. Issue 137 (April 2021) - Pamminger, Mathias; Kranewitter, Christof; Kremser, Christian; Reindl, Martin; Reinstadler, Sebastian J.; Henninger, Benjamin; Reiter, Gert; Piccini, Davide; Tiller, Christina; Holzknecht, Magdalena; Lechner, Ivan; Bauer, Axel; et al.
Highlights: 3D whole-heart MRA provides TAVI relevant aortic root measurements without contrast media administration. Self-navigated MRA enables TAVI measurements with shortened scan time and substantial larger volume coverage compared to navigator-gated MRA. Valve prothesis sizing based on self-navigated MRA is equivalent to standardized computed tomography angiography. Abstract: Objectives: To prospectively compare image-quality, reliability and graft sizing of a prototype self-navigated and a navigator-gated non-contrast three dimensional (3D) whole-heart magnetic-resonance-angiography (MRA) sequence with computed-tomography-angiography (CTA) for planning transcatheter-aortic-valve-implantation (TAVI). Methods: Self- and navigator-gated 1.5 T MRA were performed in 27 patients (aged 83 ± 5 years, 41 % male) for aortic root sizing and coronary ostia height measurements; 15 (56 %) patients underwent additional CTA. Subjective-image quality was graded on a 4-point Likert scale, objective MRA image-quality was assessed by signal-to-noise ratio (SNR) and contrast-to-noise ratio (CNR). Continuous MRA and CTA measurements were analyzed with regression and Bland-Altman analysis, valve sizing by kappa statistics. Results: Median image-quality as rated by two observers was 1.5 [interquartile range (IQR) 1–3] for self-navigated MRA and 1 [IQR 1–2] for navigator-gated MRA (p = 0.059). SNR and CNR were comparable between MRA sequences (p = 0.471 and 0.445, respectively). Acquisition time was shorter for self-navigated MRA compared to navigator-gated MRA (5.5 ± 1 min vs, 6.5 ± 2 min, p = 0.029). Inter-observer correlation of aortic root measurements was high to very high for both self- and navigator-gated MRA (r = 0.75 to 0.94 and r = 0.85 to 0.96, respectively, all p < 0.0001). Theoretical prosthetic valve sizing of self-navigated MRA and CTA was equivalent (κ = 1). However, in four patients (15 %) one coronary ostium each (right coronary artery 3, left main artery 1) was not clearly definable on self-navigated MRA. Conclusion: Self-navigated MRA enables aortic annulus TAVI measurements without significant difference to navigator-gated MRA at shortened acquisition time. Prosthesis sizing by self-navigated MRA measurements is equivalent to navigator-gated MRA and CTA-based choice.